The Blackwell companion to law and society - Sarat, Austin (Blackwell Pub., 2004)
The Blackwell Companion to Law and Society is an authoritative study of the relationship between law and social interaction. Thirty-two original essays by an international group of expert scholars examine a wide range of critical questions. Authors represent various theoretical, methodological, and political commitments, creating the first truly global overview of the field.